Outbreak of acute hepatitis A associated with men who have sex with men (MSM) in North Sardinia 2017-2018 - Riccardo Bazzardi; Elena Dore; Massimo Ciccozzi; Alessia Lai; Margherita Pisanu; Sergio Babudieri; Ivana Maida (Journal of Infection in Developing Countries)
Introduction: We describe an outbreak of hepatitis A among men who have sex with men (MSM) which evolved in Sassari (Italy), between January 2017 and December 2018, close to a contextual of large concurrent hepatitis A outbreak reported in Europe and recently, in Italy.